Derlin-1 and TER94/VCP/p97 are required for intestinal homeostasis. (March 2022) - Liu, Fuli; Zhao, Hang; Kong, Ruiyan; Shi, Lin; Li, Zhengran; Ma, Rui; Zhao, Huiqing; Li, Zhouhua
Abstract: Adult stem cells are critical for the maintenance of residential tissue homeostasis and functions. However, the roles of cellular protein homeostasis maintenance in stem cell proliferation and tissue homeostasis are not fully understood. Here, we find that Derlin-1 and TER94/VCP/p97, components of the endoplasmic reticulum (ER)-associated degradation (ERAD) pathway, restrain intestinal stem cell proliferation to maintain intestinal homeostasis in adult Drosophila . Depleting any of them results in increased stem cell proliferation and midgut homeostasis disruption. Derlin-1 is specifically localized in the ER of progenitors, and its C-terminus is required for its function. Interestingly, we find that increased stem cell proliferation is resulted from elevated ROS levels and activated JNK signaling in Derlin-1 - or TER94 -deficient progenitors. Further removal of reactive oxygen species (ROS) or inhibition of JNK signaling almost completely suppresses increased stem cell proliferation. Together, these data demonstrate that the ERAD pathway is critical for stem cell proliferation and tissue homeostasis. Thus, we provide insights into our understanding of the mechanisms underlying cellular protein homeostasis maintenance (ER protein quality control) in tissue homeostasis and tumor development.